Resources for the evaluation of the effectiveness of a Kaizen program aimed at reducing Lead Time - Martins, Thiago Loretti Arico; Azevedo, Marilia Macorin de (Brazilian Journal of Production Engineering, 2025)
This article proposes resources for evaluating the effectiveness of a Kaizen program in reducing lead time in a process for manufacturing professional uniforms. Through a case study conducted at Alpha, the periods before and after the adoption of the Kaizen program were compared, with the aim of measuring its impacts on production performance. The analysis focused on nonparametric data, using statistical tools such as descriptive statistics, histograms, time series graphs, verification of data normality with the Anderson-Darling test, as well as the application of the nonparametric Mann-Whitney test to investigate potential differences between the scenarios evaluated. The results indicated a reduction in lead time and a decreasing trend over time, although the statistical analysis did not reveal significant differences. Given the lack of standardized criteria for the objective measurement of the effectiveness of Kaizen, the study proposes a set of analytical instruments that allow for the systematic evaluation of improvements in production processes. In this way, it contributes to the advancement of research on continuous improvement, offering theoretical and practical support applicable in similar industrial contexts.
Keywords: Kaizen; Mann-Whitney U; lead time; normality test; Histogram